The Role of Lymph Node Dissection in the Treatment of Bladder Cancer - Cattaneo, Francesco; Motterle, Giovanni; Zattoni, Filiberto; Morlacco, Alessandro; Dal Moro, Fabrizio (Frontiers in Surgery, 2018)
Lymph node dissection (LND; PLND: pelvic LND) is an essential component of radical cystectomy (RC) for bladder cancer (BC). However, the optimal anatomical extent of LND and its potential therapeutic role are still controversial: as we will explain, the extent of LND dissection is a predictor of survival and local recurrence but what is an adequate extension is still unclear. Moreover, there is large uncertainty about the role of surgery in patients with clinically-positive nodes. In this review we will provide a synthesis of the available evidence on this highly debated topic. Overall, the studies presented in this work support the idea that extended lymphadenectomy could provide optimal diagnostic and possibly therapeutic results in cN- patients. In cN+ patients, post chemotherapy surgery may be considered especially in subjects who have a good response to CHT, although definitive evidence is still needed. Finally, the final results of randomized trials are eagerly awaited to draw definitive conclusions of the role of PLND in BC.